Catecholamine responses to virtual combat: implications for post-traumatic stress and dimensions of functioning - Highland, Krista B.; Costanzo, Michelle E.; Jovanovic, Tanja; Norrholm, Seth D.; Ndiongue, Rochelle B.; Reinhardt, Brian J.; Rothbaum, Barbara; Rizzo, Albert A.; Roy, Michael J. (Frontiers in Psychology, 2015)
PTSD symptoms can result in functional impairment among service members (SMs), even in those without a clinical diagnosis. The variability in outcomes may be related to underlying catecholamine mechanisms. Individuals with PTSD tend to have elevated basal catecholamine levels, though less is known regarding catecholamine responses to trauma-related stimuli. We assessed whether catecholamine responses to a virtual combat environment impact the relationship between PTSD symptom clusters and elements of functioning. Eighty-seven clinically healthy SMs, within 2 months after deployment to Iraq or Afghanistan, completed self-report measures, viewed virtual-reality (VR) combat sequences, and had sequential blood draws. Norepinephrine responses to VR combat exposure moderated the relationship between avoidance symptoms and scales of functioning including physical functioning, physical-role functioning, and vitality. Among those with high levels of avoidance, norepinephrine change was inversely associated with functional status, whereas a positive correlation was observed for those with low levels of avoidance. Our findings represent a novel use of a virtual environment to display combat-related stimuli to returning SMs to elucidate mind-body connections inherent in their responses. The insight gained improves our understanding of post-deployment symptoms and quality of life in SMs and may facilitate enhancements in treatment. Further research is needed to validate these findings in other populations and to define the implications for treatment effectiveness.